The Planispheric Optic Array - Jan Koenderink; Andrea van Doorn (i-Perception, 2017)
The “planispheric optic array” is a full-horizon Mercator projection of the optic array. Such pictures of the environment are coming in common use with the availability of cheap full-view cameras of reasonable quality. This introduces the question of whether the public will actually profit from such pictorial information in terms of an understanding of the spatial layout of the depicted scene. Test images include four persons located at the corners of a square centered at the camera. The persons point at each other in various combinations. Participants in the experiment judge who is pointing at whom in a number of such photographs. It is found that certain very systematic and huge errors are the rule, indicating that naïve viewers are quite unable to parse such planispheric representations.